Analyst monitoring and information asymmetry reduction: U.S. evidence on environmental investment - Lewis Liu (Innovation and Green Development, 2024)
This study examines the connection between analyst coverage and environmental investment using firm-level data from the S&P 500 spanning 2001 to 2022. There is still an unclear and missing piece in the literature of the U.S. evidence investigating the impact of external analysts on monitoring corporate sustainable development. Building upon prior research and filling in the gap, this study proposes that analyst coverage can affect corporate environmental investment and reduce information asymmetry. The findings demonstrate that analysts act as external monitors, reducing information asymmetry and enhancing environmental investment. To strengthen the main conclusions, the study utilizes various robustness tests, including propensity score matching (PSM), 2SLS instrument variable approach, and subsample analysis. In aggregate, the study contributes to the growing body of literature on the important monitoring role of analysts in promoting sustainable business practices and reducing information asymmetry. It offers valuable insights for policymakers and investors to promote sustainable practices and reduce information asymmetry.